Review of water treatment technologies for PFAS from a life cycle perspective, with meta-analysis of financial costs and climate impacts - Sabrina Altmeyer Mendes; Rahul Aggarwal; Magdalena Svanström; Gregory Peters (Resources, Conservation and Recycling, 2025)

Loss-on-Drying Prediction for a Vibrated Fluidised Bed Dryer by Means of Mass and Energy Balances - Katharina Kiricenko; Felix Hartmann; Andreas Altmeyer; Peter Kleinebudde (Journal of Pharmaceutical Innovation, 2023)
Purpose Continuous wet granulation and drying require an adequate process control strategy to ensure the product quality. The most important critical quality attributes of dried granules are the granule size distribution and moisture content. Process analytical technologies (PATs) are available for real-time monitoring of moisture content by, e.g., near-infrared spectroscopy (NIRS), which requires additional installation and complex multivariate validation. Thus, a mass and energy balance (MEB) was derived for a vibrated fluidised bed dryer, which is part of the QbCon ® 1 intended for continuous wet granulation and drying. Method Process parameters that are frequently logged were used for the derivation of a MEB. The predicted MEB was compared with the measured loss-on-drying (LOD) for two different formulations. Results The model-derived data were in good agreement with the observed LOD, leading to RMSE values of 0.12–0.45. Conclusion The implemented MEB can predict the LOD over time and thus might be suitable as a soft sensor without the installation of additional sensors. The obtained energy flux gives insight into the heat transfer, and the derived energy balance might be used to determine the required energy under certain drying conditions.

Comparative microarray analysis of microRNA expression profiles in primary cutaneous malignant melanoma, cutaneous malignant melanoma metastases, and benign melanocytic nevi - Michael Sand; Marina Skrygan; Daniel Sand; Dimitrios Georgas; Thilo Gambichler; Stephan A. Hahn; Peter Altmeyer; Falk G. Bechara (Cell and Tissue Research, 2013)

The miRNA machinery in primary cutaneous malignant melanoma, cutaneous malignant melanoma metastases and benign melanocytic nevi - Michael Sand; Marina Skrygan; Dimitrios Georgas; Daniel Sand; Thilo Gambichler; Peter Altmeyer; Falk G. Bechara (Cell and Tissue Research, 2012)

Fluorescence Studies of Melanin by Stepwise Two-Photon Femtosecond Laser Excitation - Klaus Teuchner; Jürgen Ehlert; Wolfgang Freyer; Dieter Leupold; Peter Altmeyer; Markus Stücker; Klaus Hoffmann (Journal of Fluorescence, 2000)